Frontispiece: Combined Spectroscopic and Electrochemical Detection of a NiI⋅⋅⋅HN Bonding Interaction with Relevance to Electrocatalytic H2 Production. Issue 29 (13th July 2015) - Kochem, Amélie; O'Hagan, Molly; Wiedner, Eric S.; van Gastel, Maurice
<x xml:space="preserve">Abstract</x> Electrochemistry In electrocatalytic production of H2 by [Ni(PR2NR′2)2]2+ complexes, protonation of the NiI intermediate is a critical step that influences the efficiency of catalysis. In their Full Paper on page 10338 ff., E. S. Wiedner, M. van Gastel et al. investigate this reaction step by using cyclic voltammetry and hyperfine sublevel correlation (HYSCORE) spectroscopy. These studies revealed that protonation occurs at a pendant amine that is endo to NiI due to formation of an intramolecular NiI⋅⋅⋅HN bonding interaction. Importantly, this places the proton in the ideal position for ultimate formation of a HH bond at the Ni center.